Modeling the Domestic Distribution Network for Illicit Drugs - Caulkins, Jonathan P. (Management Science, 1997)
This paper presents a simple economic model of a drug dealer's decision about how many customers to supply. The model relates the number of customers (i.e., the branching factor of the distribution network) to a quantity discount factor describing the extent to which prices are marked up from one distribution level to the next and the ratio of selling costs to product costs. Solving the model allows one to infer characteristics of the domestic distribution network from more readily observable characteristics of the markets and, thereby, to gain insight into how drug control interventions might work.